Geometrical Optimization of the Induction Heating Process in Order to Achieve Uniform Gloss on Plastics Components - Gasparec, Andrej; Saga, Milan (Manufacturing Technology Journal, 2015)
The article deals with numerical simulation of induction heating process as a coupling of electromagnetism and heat transfer with the scope to surface temperature optimization. The article presents how the position of the inductors used in the induction heating process influence the resulting temperature of heated surface. The scope of the article is to show methodology to optimize surface temperature by numerical approach.
Keywords: Induction heating; Electromagnetic field analysis; Thermal analysis; Optimization